2008
DOI: 10.1016/j.febslet.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XVI expression is upregulated in glioblastomas and promotes tumor cell adhesion

Abstract: The poor prognosis of glioblastoma patients is related to diffuse brain invasion and interaction of tumor cells with extracellular matrices (ECM). We describe expression and function of the FACIT-collagen XVI in glioblastomas. We found upregulation of collagen XVI mRNA as well as protein in glioblastomas as compared to normal cortex. SiRNA knockdown resulted in decreased cell adhesion whereas increased adhesion was observed on surfaces coated with collagen XVI. The migration of glioblastoma cells on this subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…We demonstrated a strong upregulation of collagen XVI in glioblastoma tissue, which is characterized by aggressive tumour cell invasion into its surrounding tissue. Using glioma cell lines as model system we observed that collagen XVI ameliorates adhesion of these cells to matrix with the glioma cell line U87MG showing strongest adhesion on collagen XVI among all tested glioma cell lines [11].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We demonstrated a strong upregulation of collagen XVI in glioblastoma tissue, which is characterized by aggressive tumour cell invasion into its surrounding tissue. Using glioma cell lines as model system we observed that collagen XVI ameliorates adhesion of these cells to matrix with the glioma cell line U87MG showing strongest adhesion on collagen XVI among all tested glioma cell lines [11].…”
Section: Introductionmentioning
confidence: 91%
“…5x10 5 cells per reaction were incubated with 80 pmol of siRNA (8pmol / μl) and 100 μl Nucleofector solution and run on program X-01. The cells were transfected with two collagen XVI-specific siRNAs: siRNA1 (5'-uga gcu cau uga gau caa u dTdT-3') and siRNA2 (5'-gga cuc aaa uug gaa cac a dTdT-3') and the corresponding sequences as double strand; as well as scrambled siRNA (control) as described elsewhere [11]. All siRNAs were purchased from Qiagen, Hilden, Germany.…”
Section: Transfectionmentioning
confidence: 99%
“…However, the migration potential of glioblastoma cells on collagen type XVI remained unaffected. Collagen type XVI appears to play a supportive role for tumour specific remodelling of extracellular matrix indicated through de novo expression by glioblastoma cells (Senner et al, 2008). Novel data suggest that in glioblastoma tissue collagen XVI may impair the cell-cell interaction in favour of enhancement of invasion.…”
Section: Notementioning
confidence: 97%
“…It is synthezised by dermal fibroblasts, smooth muscle cells (Grässel et al, 1996), dermal dendrocytes and dendritic cells in the skin (Akagi et al, 2002), articular and costal chondrocytes (Kassner et al, 2003), endometrial stromal cells (Tierney et al, 2003), basal dermal and oral keratinocytes (Grässel et al, 1999), bone marrow derived mesenchymal stem cells (Grässel et al, 2009), neurons from the dorsal root ganglion (Hubert et al, 2007), glioblastoma/astrocytoma cells (Senner et al, 2008) and intestinal myofibroblasts (Ratzinger et al, 2010). Collagen type XVI is further expressed in the limbal stem/progenitor niche which comprises clusters of cells in the basal epithelium.…”
Section: Expressionmentioning
confidence: 99%
See 1 more Smart Citation